Lecturers’ financial wellness: The role of religiosity, financial literacy, behavior, and stress with gender as the moderating variable - Susnaningsih Muat; Khairil Henry (Journal of Accounting and Investment, 2023)
Research aims: The study’s objective is to propose and empirically test a model encompassing financial literacy, financial behavior, financial stress, religiosity, and the role of gender as moderating variable on financial wellness.Design/Methodology/Approach: Using a convenience sampling technique, an online survey was conducted to collect data from lecturers in Pekanbaru, yielding 116 usable responses that were analyzed using partial least squares structural equation modeling (PLS-SEM).Research findings: The study findings highlighted that financial behavior and religiosity positively impacted financial wellness, while financial stress significantly negatively influenced financial wellness. The study also confirmed the moderation role of gender in the relationship between financial literacy and financial wellness.Theoretical contribution/Originality: This study’s findings contribute to the literature by examining the role of religiosity as the determinant of financial wellness among lecturers. Specifically, this study provides new insight into lecturers’ financial wellness because most previous studies focus on employeesResearch limitation/Implication: This cross-sectional study was conducted at a specific time, so the causal relationships could not be established. Hence, researchers in the future may employ a longitudinal strategy to analyze changes in financial behavior and their effects across time